Development of Graphene Related Solid Lubricant Coating - Avissery Narayanankutty, Arun (My University, 2026)
Tribological coatings are important for improving performance and service life by reducing friction and wear in mechanical systems across several industries. Making composite coatings that balance tribological and electrical properties can improve mechanical strength, durability, and electrical performance with positive effects on energy efficiency and material use. Graphene is known for its good structural, electrical, thermal, and lubrication properties. One of its derivatives- reduced graphene oxide (RGO), has a similar structure and properties. In this work, the aim was to make composite coatings by combining the ability of graphene- related materials with polymers and metals. RGO- polymer composite coatings were prepared using direct application and dip coating methods. In parallel, RGO- copper (Cu) multilayer composites were developed using surface modification, direct application, and electroplating processes. Among the samples, RGO- Cu coatings showed better overall results. Coatings with one to five layers were made on steel and copper substrates. Tribological, electrical, adhesion tests were carried out on the samples and characterization techniques used to analyze the properties. RGO outer layers on steel showed good friction performance but were electrically insulating. Cu outer layers gave better electrical properties but inferior wear properties. RGO layer interfacial bonding over Cu coating seems weak.
Keywords: graphene; surface technology; coating; tribology; composite; process development; testing; characterization